The Effectiveness of Using Color-Coding in Teaching Grammar for Female Saudi EFL Learners in KSA - Mohammad Aljehani, Layla (International Journal of English Language Education, 2022)
This study explores the effect of using color-coding teaching techniques on L2 learners’ accuracy of using English articles and quantifiers by employing a mixed method research design. The study aims to answer two research questions. The first research question explores the effect of color-coding grammar instruction on Saudi EFL learners’ accuracy of article and quantifier use. The second question explores the perception of Saudi EFL learners towards color-coding grammar instruction. To answer the first question of the study, a classroom experiment was conducted. To answer the second research question, interviews were conducted. The sample consisted of 82 Saudi female intermediate level students who are preparatory year students and taking general English language courses at the English Language Institute, King Abdulaziz University. The classroom experiment showed that there is a statistical significate in that the experimental group outperformed the control group which suggests that color-coding is effective for teaching English articles and quantifiers. Moreover, it was found that all the participants seem to prefer to learn by using colors more than black and white colors scheme. Based on these findings, it is recommended that English instructional material is better learned when presented or enhanced using color-coding techniques compared with black and white color scheme.